#TITLE_ALTERNATIVE# - Sarie NIM : 25099034, Fatma
Abstract: The aims of this research is evaluating the effect of berm size and strength in limiting deformation as a temporary restraint toward sheet piles before the next construction, particularly in basement construction. The analysis case is an excavation of a basement with LX32 sheet piles. The analyzed soil is dense sands consist of 4, = 32 derajat and c = 1 kN/m where the soil modeling is Hardening-Soil applied as data input for Plaxis Program. Dimensions of berms are limited by changing the slope of the berms as 1:2, 1:3, and 1:4. The berms used in the analyses are assumed to be triangular and trapezium in shape. Also, in order to establish limiting behavior, a no berm case and a horizontal berm case are analyzed for each excavation. The wall is assumed to either fully penetrate (fixed end wall) also partially penetrate (free end wall) the sand layer. The results demonstrate that increasing berm size serves to decrease movements of wall systems and vertical displacements behind wall systems. However, the effects of the berm are not a unique function of the berm size. It is also influenced by wall stiffness; excavation depth, wall end conditions assumption and soil shear strength. The safety factor of wall-soil system decrease as the berm slope steepened. Restraint force of berm as passive force for the wall-soil system can control the stability of-sheet piles wall effectively. Contribution of berm as passive restraint force on sheet piles wall for analyzed cases between 49.5%-99.8%.